Kajian Sosiolinguistik terhadap Tuturan Makian Masyarakat Heterogen di Medan - Sitompul, Ayu Wardani; Ginting, Christine Hagaina; Sihite, Theresa Da Silvia; Harahap, Safinatul Hasanah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In general, humans interact to foster cooperation between each other to form, develop and pass on their culture in the broadest sense. In everyday life, of course, we don't just use formal language. When you are angry, the language used tends to be stiff and also has connotations. This research was conducted because swear words are not only used when angry, but swear words are also used in intimate and relaxed situations. Swear words also have the aim of insulting, belittling, expressing disappointment, admiration/surprise and praise. This research refers to a qualitative approach and uses two methods, namely the proficient free-involved listening method and the note-taking method. In this research, it is a method carried out by listening which is paralleled with observation, showing and studying carefully the object under study, the researcher records swearing in busy situations, the swearing data is then recorded in a data folio for analysis. The data analysis method used is the extralingual matching method. The results of the research show that Medan people mostly use swear words, almost eighty-five percent. Meanwhile, fifteen percent of Medan people use swear words in the form of phrases.